Elaboração do mapa de riscos em um laboratório de análises clínicas - Neres, Roseane Fernandes (Universidade Federal Rural do Semi-Árido, 2018)
In view of the current scenario, where there is a great concern with Occupational Safety, a detailed analysis is necessary, because working safely brings benefits to both the worker and the company. In a laboratory environment of clinical analysis, a series of activities with different degrees of complexity are integrated, connected by a vast diversification of procedures with exposure to the risks of accidents inherent in the work performed. Therefore, analyzing the security established during the work is extremely important. There is a need to verify that they are complying with the Regulatory Norms or if they are taking susceptible risks that compromise their health. The various norms applied in this study are intended to observe the protection of workers within the laboratory. In view of this, a Risk Map was prepared for the laboratory with the purpose of raising workers' awareness of the risks they are exposed to, as well as eliminating or reducing them caused during the exercise.
Monografia
Keywords: Segurança do Trabalho; Riscos de acidentes; Prevenção; Mapa de riscos; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA